Treatment of Chronic Urticaria - Jurakić-Tončić, Ružica (Array, 2009)
Summary:Urticaria is a disorder characterized by rapid onset of localized swelling of the skin or mucosa, called wheals or urtica. According to frequency and duration, urticaria can be divided into acute and chronic type. Chronic urticaria is any type of urticaria occurring every day or twice per week, lasting longer than 6 weeks. Chronic urticaria is a common disorder and estimated prevalence is 1% of the population. Also, it is not rare in childhood. The pathogenesis of chronic urticaria has not yet been completely understood. Chronic urticaria is a heterogeneous group of disorders, and according to the etiology and cause, several groups of chronic urticaria are distinguished, i.e. autoimmune, pseudoallergic, infection-related, physical urticaria, vasculitis urticaria and idiopathic urticaria. Treatment and management of chronic urticaria can be non-pharmacological and pharmacological, and sometimes it is not possible to control the disease with antihistamines only, which are considered to be the mainstay of treatment. In severe cases of chronic urticaria, especially if autoimmunity has been proven, several authors describe different modules of immunomodulation: cyclosporine, cyclophosphamide, mycophenolate- mofetil, omalizumab, plasmapheresis, systemic corticosteroids, and immunoglobulin therapy. This article primarily addresses the treatment of chronic idiopathic and autoimmune urticaria